2014
DOI: 10.1093/jpepsy/jsu004
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Bias to Activity of Different Parts of the Body in Children With Functional Abdominal Pain: An Experimental Study

Abstract: Children with FAP seemed more strongly influenced by information about gut activity than healthy children. The present study should be replicated for intervention purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…A second study, which did use a pain-free comparison group [1], reported greater attention for pain-related words in patients with functional abdominal pain (aged 10-16 years) at both brief (20ms) and long (1250ms) presentation times, but only after a laboratory stressor (failure versus success feedback regarding their performance on a challenging computer game). A subsequent study, also of patients (aged 8-17 years) with functional abdominal pain reported no attention biases for pictorial stimuli depicting pain in either group [69] at either brief (20ms) or long (1250ms) presentation times. Most recently, a study assessed selective attention bias for pain-related faces (presented for 500ms) amongst patients with chronic pain aged 10-18 years in the context of a larger attention training controlled trial (for the reduction of pain symptoms) [30].…”
Section: Attention Biasesmentioning
confidence: 84%
See 1 more Smart Citation
“…A second study, which did use a pain-free comparison group [1], reported greater attention for pain-related words in patients with functional abdominal pain (aged 10-16 years) at both brief (20ms) and long (1250ms) presentation times, but only after a laboratory stressor (failure versus success feedback regarding their performance on a challenging computer game). A subsequent study, also of patients (aged 8-17 years) with functional abdominal pain reported no attention biases for pictorial stimuli depicting pain in either group [69] at either brief (20ms) or long (1250ms) presentation times. Most recently, a study assessed selective attention bias for pain-related faces (presented for 500ms) amongst patients with chronic pain aged 10-18 years in the context of a larger attention training controlled trial (for the reduction of pain symptoms) [30].…”
Section: Attention Biasesmentioning
confidence: 84%
“…However, because most of the studies used similar age ranges, it is difficult to attribute differences in results across studies to differences in age. However, where studies did investigate the main effects of age on bias [3,69], these effects were non-significant. A final possibility is that attention biases are as weak in this age range as they are in adults, and may not contribute to pain outcomes.…”
Section: Attention Biasesmentioning
confidence: 99%
“…Our findings also extend understanding of cognitive factors in pediatric pain. Previous studies have indicated that youth with chronic pain are characterised by biases in the way they attend to [3,4,24,63] and remember [32] pain-related information. We present here evidence that biased interpretations of ambiguous bodily-threat information are also relevant for the experience of chronic pain in youth.…”
Section: Discussionmentioning
confidence: 99%
“…These effects may be attributable to increased avoidance of health-threat rather than engagement with it (De Ruiter and Brosschot, 1994), however, or stimulus negativity more generally (Posserud et al, 2009). Studies using the dot-probe and exogenous cueing paradigms have not found evidence of attentional bias in MUS patients (Chapman and Martin, 2011;Hou et al, 2008;Martin and Alexeeva, 2010;Martin and Chapman, 2010;van der Veek et al, 2014;Witthöft et al, 2006).…”
Section: Interoceptive Hypervigilance Thresholds and Awarenessmentioning
confidence: 95%